Comparative evaluation of weight bearing exercise and vestibular stimulation on balance in children with down syndrome - Dr. K. KAMATCHI; Dr. V. BALACHANDAR; Dr. N. KAVIRAJA (International Journal of Pharma and Bio Sciences, 2018)
Down syndrome (DS) is one of the common genetic disorders prevailing in the human population caused by trisomy of the chromosome number 21. The affected individuals exhibit physical, neurological and cognitive impairment. The present study was intended to compare the effectiveness of weight bearing exercise (WBE) with vestibular stimulation (VS) on balance in children with DS. The research involved 30 subjects of 6-9 years of age with medically diagnosed Down syndrome and with IQ more than or equal to 50. The subjects were randomly distributed into two groups. Group I was assigned with WBE and Group II with VS to improve balance. The pre-test and post-test balance of the subjects was measured using Pediatric Balance Scale (PBS). Intervention was applied daily for six weeks; both the groups were subjected to 30 min of approximation and strengthening exercise followed by 5 min rest. The result revealed a significant improvement in balance of children in both the groups. The mean PBS score of the Group I subjects was 16.33 and that of Group II 30. 73, indicating the higher effectiveness of VS over WBE in improving the balancing abilities of the DS children. Therefore the study has concluded that VS is more effective than the WBE in improving the balance in subjects with DS.